Strategi pengembangan usaha mikro kecil dan menengah berbasis ekonomi kreatif - Achmad Zaki (IKIP SILIWANGI, 2023)
This community service activity aims to:The implementation of community service is located at UPN Veteran Surabaya, the target of implementing the service is participants in the Nusantara Module program MBKM (Freedom Learning Campus Merdeka) UPN Veteran East Java Surabaya in the archipelago module activities. The method used in this community service activity is to use the extension method as an effort to increase the awareness of the participants in the Nusantara Module MBKM program on the development of micro, small and medium enterprises based on a creative economy by utilizing digital marketing. Evaluation is carried out by looking at the level of success of the activity starting from the beginning of the activity, the process of the activity to the achievement of the activity by asking for advice and input in the form of testimonials from all activity participants. The results show that there is an increase in theoretical knowledge and practice of developing creative economy-based learning SMEs. This matterefforts to increase the awareness of participants in the Nusantara Module MBKM program on the development of creative economy-based MSMEs by utilizing digital marketing